(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Gastrointestinal endoscopy is one of the main diagnostic tools for gastrointestinal examination. In this study, we measured the effect pre- procedure education on the readiness of patients for the endoscopy. Method: This quasi-experimental study was performed on 70 patients aged 35-60 years who were candidates for endoscopy from SEP 2018 to MAY 2019. Data were collected by a valid and reliable, 22 items’ questionnaire that developed by the researcher. Data were analyzed by SPSS, version 16. Results: mean score of readiness for endoscopy in the intervention group 105.8 (5.3) was significantly higher than control group 62.6 (7.8), (p<0.001). Also, the level of readiness of the intervention group was 11.4% good and 88.6% very good. The level of readiness of the control group was 91.4% moderate and 8.6% good. Conclusions: Considering the effect of pre- procedure education on the readiness of patients for the endoscopy, it can be inferred that providing educational programs before endoscopy can be helpful.